2012
DOI: 10.7705/biomedica.v32i4.773
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización de la transmisión de la malaria por Plasmodium vivax en la región fronteriza de Panamá con Costa Rica en el municipio de Barú, Panamá

Abstract: Contribución de los autores:Todos los autores contribuyeron en la redacción y corrección del manuscrito, análisis e interpretación de los datos, verificación de referencias bibliográficas, observaciones y revisión crítica del mismo. ARTÍCULO ORIGINAL Biomédica 2012;32:557-69 doi: http://dx.doi.org/10.7705/biomedica.v32i4.773 Caracterización de la transmisión de la malaria por Plasmodium vivax en la región fronteriza de Panamá con Costa Rica en el municipio de Barú, Panamá Characterization of Plasmodium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 23 publications
1
11
0
6
Order By: Relevance
“…In this series, although the frequency was low, the number of mixed malaria cases (due to P. vivax and P. falciparum, 5.4%) was quite high compared to other studies in Latin America, which usually have reported less than 2% [7,[26][27][28]. However, the mixed malaria cases were those that most frequently presented complications and required the patient to be hospitalized in this study (crude OR = 5.535; 95%CI 1.81-16.9).…”
Section: Discussionmentioning
confidence: 45%
“…In this series, although the frequency was low, the number of mixed malaria cases (due to P. vivax and P. falciparum, 5.4%) was quite high compared to other studies in Latin America, which usually have reported less than 2% [7,[26][27][28]. However, the mixed malaria cases were those that most frequently presented complications and required the patient to be hospitalized in this study (crude OR = 5.535; 95%CI 1.81-16.9).…”
Section: Discussionmentioning
confidence: 45%
“…Estas zonas endémicas se localizan en las cercanías de las regiones fronterizas de Panamá con Costa Rica y Colombia (6 (2009)(2010)(2011)(2012)(2013), en estas regiones endémicas que ocupan el 38,6 % del territorio nacional y tienen una población de 858.121 habitantes (7), se registraron 3.099 casos de malaria, con un promedio anual de 620 casos. Durante este periodo la incidencia parasitaria anual promedio fue de 0,2 por 1.000 habitantes, el índice de láminas positivas fue de 0,5 %, el índice anual de exámenes de sangre fue de 3,6 %, la tasa de morbilidad promedio fue de 17,2 por 1.000 habitantes, y no se registraron muertes; el 99 % de los casos fueron por P. vivax (4).…”
unclassified
“…Durante este periodo la incidencia parasitaria anual promedio fue de 0,2 por 1.000 habitantes, el índice de láminas positivas fue de 0,5 %, el índice anual de exámenes de sangre fue de 3,6 %, la tasa de morbilidad promedio fue de 17,2 por 1.000 habitantes, y no se registraron muertes; el 99 % de los casos fueron por P. vivax (4). Anopheles albimanus es considerado como el principal vector del paludismo en el país (6,8).…”
unclassified
“…P. vivax generates more than 90% of the cases, with periodic outbursts of Plasmodium falciparum , mainly from cases imported from other countries [22]. In the indigenous regions, more than 85% of cases are diagnosed at the national level, representing 12% of the total population of the country [22]. Malaria is a challenge for public health professionals due to high level of mortality and morbidity in this area of the Americas [23].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, 78% perform traditional practices such as ‘Smoking of the Pipe’ and ‘Burning of the Cocoa and Pepper’ to prevent malaria [34]. Other indigenous groups of the country have specialists divided into several disciplines that are in charge of curing diseases through a direct relation with the spirits [22]. …”
Section: Discussionmentioning
confidence: 99%